2019
DOI: 10.1503/cjs.008718
|View full text |Cite
|
Sign up to set email alerts
|

How accurate are we? A comparison of resident and staff physician billing knowledge and exposure to billing education during residency training

Abstract: Background: Practice management is an overlooked and undertaught subject in medical education. Many physicians feel that their exposure to billing education during residency training was inadequate. The purpose of this study was to compare resident and staff physicians in terms of their billing knowledge and exposure to billing education during residency training. Methods: Senior residents and staff physicians completed a scenario-based clinical billing assessment. Posttest surveys were completed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…This study has shown that further training in “billing and coding” was the most highly prioritized of the 8 core business principles by Canadian plastic surgery residents. A study by Austin and von Schroeder 5 compared billing knowledge and accuracy amongst a group of 16 senior surgical residents and 17 staff surgeons. This study found that while staff physicians had a greater accuracy that residents on a billing assessment with more correct codes and fewer incorrect or missed codes, the overall billing accuracy in both groups was poor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has shown that further training in “billing and coding” was the most highly prioritized of the 8 core business principles by Canadian plastic surgery residents. A study by Austin and von Schroeder 5 compared billing knowledge and accuracy amongst a group of 16 senior surgical residents and 17 staff surgeons. This study found that while staff physicians had a greater accuracy that residents on a billing assessment with more correct codes and fewer incorrect or missed codes, the overall billing accuracy in both groups was poor.…”
Section: Discussionmentioning
confidence: 99%
“…In the current model of medical education, there is a predominant focus on clinical competency, while the nonclinical aspects of medical practice, including business and practice management, go overlooked and undertaught. 4 , 5 Studies have shown that trainees and graduates from a variety of subspecialty training programs report inadequate exposure to practice management education during their residency training, even though these trainees feel that this education is important for establishing and maintaining a medical practice after residency. 5-11 Interestingly, surveys of residency program directors and educators have also demonstrated an acknowledgment for the importance of practice management education in residency training programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2016, we found an increase in the number of U.S studies on this topic, where results have echoed earlier findings that the level of medical billing literacy amongst medical practitioners remains demonstrably low and may be improved by targeted education. [11][12][13][14][15] In one recent U.S study more than 70% of medical practitioner participants felt there was a need for medical billing and coding to be included in the medical curriculum 16 and a 2019 study of senior residents and staff physicians in Ontario, Canada (n=33) 17 described the billing accuracy of the medical practitioner participants as poor overall, with billing errors and omissions causing substantial revenue losses. Participants in that study felt that current medical billing education was both insufficient and ineffective and desired more.…”
Section: Empirical Literature -Us and Canadamentioning
confidence: 99%
“…The common reasons for improper payments were insufficient documentation errors (64.1%), medical necessity errors (17.5%), incorrect coding errors (13.1%), and no documentation errors (1.7%) [8]. With regard to the effort of evaluating coding errors, numerous studies have associated physicians' limited training and knowledge of billing and insurance-related activities with high errors [9][10][11][12]. King et al [10] showed that family physicians' coding accuracy was 52% for established patients and 17% for new patients, as established patients were undercoded, thus failing to report the full services provided, whereas new patients were overcoded, an abuse in reporting medical services not actually performed.…”
Section: Introductionmentioning
confidence: 99%